The use of Monte Carlo simulation technique to support investment decisions - Tamošiūnienė, Rima; Petravičius, Tomas (Business: Theory and Practice, 2006)
In this paper the methodology and uses of Monte Carlo simulation technique in the evaluation of investment projects are presented to analyse and assess the risk. The first part presents the theoretical background of Monte Carlo analysis in various process stages. The second part examines the interpretation of the results generated by the application of project formulation, financial and risk analysis including investment decision criteria and measures of risk based on the expected NPV value concept. The final part draws some conclusions regarding the usefulness and limitations of Monte Carlo analysis in investment appraisal.